2005
DOI: 10.1007/s00467-005-2083-6
|View full text |Cite
|
Sign up to set email alerts
|

May we go on with antibacterial prophylaxis for urinary tract infections?

Abstract: Recurrent urinary tract infections (UTIs), with or without vesicoureteric reflux (VUR), are by far the most frequent reason for long-term antibacterial prophylaxis in infants and children today. However, the strategies of antibacterial prophylaxis for the prevention of recurrent urinary tract infection are no longer universally accepted. In infants and children at risk, the benefits of antibacterial prophylaxis definitively are not yet proven by evident data. To put antibacterial prophylaxis in its place, risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 73 publications
2
56
1
8
Order By: Relevance
“…GU anomalies, including voiding dysfunction, contribute to urine stasis, which is a major factor of both UTI and recurrent UTI. 13 Our study showed that once UTI occurs in a child, the chance of recurrence is almost 20% in both boys and girls. GU anomalies, especially VUR, were the most significant independent risk factors.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…GU anomalies, including voiding dysfunction, contribute to urine stasis, which is a major factor of both UTI and recurrent UTI. 13 Our study showed that once UTI occurs in a child, the chance of recurrence is almost 20% in both boys and girls. GU anomalies, especially VUR, were the most significant independent risk factors.…”
Section: Discussionmentioning
confidence: 55%
“…Some studies have questioned the efficacy of antibiotic prophylaxis in patients with recurrent UTI, 6,13 but to date, none have been conclusive. One meta-analysis review concluded that antibiotic prophylaxis "may not" prevent recurrent symptomatic UTI on children.…”
Section: Discussionmentioning
confidence: 99%
“…Searching the literature up to 2006, an extensive editorial commentary in this journal [9] reported that, while the strategies of antibacterial prophylaxis for the prevention of recurrent urinary tract infection were no longer universally accepted, recurrent urinary tract infections, with or without reflux, remained the most frequent reason for long-term antibacterial prophylaxis in infants and children. A recent Cochrane review [10] concluded that the small number of poor quality studies gave no reliable evidence of the effectiveness of antibiotics in preventing recurrent symptomatic UTIs.…”
mentioning
confidence: 99%
“…Lebensjahrs die antibakterielle Infektionsprophylaxe auch bei persistierendem VUR versuchsweise zu beenden. Dies gilt insbesondere für Kinder mit niedriggradigen VUR (I-III) [2].…”
Section: Wie Lange Sollte Beim Vesikoureteralen Reflux Eine Antibakteunclassified